Promising Natural Products in New Drug Design, Development, and Therapy for Skin Disorders: An Overview of Scientific Evidence and Understanding Their Mechanism of Action - Nurul Amirah, Mohd Zaid; Mahendran, Sekar; Bonam, Srinivasa Reddy; Gan, Siew Hua; Lum, Pei Teng; Begum, M Yasmin; Nur Najihah, Izzati Mat Rani; Vaijanathappa, Jaishree; Wu, Yuan Seng *; Vetriselvan, Subramaniyan; Fuloria, Neeraj Kumar; Fuloria, Shivkanya (Dove Press, 2022)
The skin is the largest organ in the human body, composed of the epidermis and the dermis. It provides protection and acts as a barrier against external menaces like allergens, chemicals, systemic toxicity, and infectious organisms. Skin disorders like cancer, dermatitis, psoriasis, wounds, skin aging, acne, and skin infection occur frequently and can impact human life. According to a growing body of evidence, several studies have reported that natural products have the potential for treating skin disorders. Building on this information, this review provides brief information about the action of the most important in vitro and in vivo research on the use of ten selected natural products in inflammatory, neoplastic, and infectious skin disorders and their mechanisms that have been reported to date. The related studies and articles were searched from several databases, including PubMed, Google, Google Scholar, and ScienceDirect. Ten natural products that have been reported widely on skin disorders were reviewed in this study, with most showing anti-inflammatory, antioxidant, anti-microbial, and anti-cancer effects as the main therapeutic actions. Overall, most of the natural products reported in this review can reduce and suppress inflammatory markers, like tumor necrosis factor-alpha (TNF-α), scavenge reactive oxygen species (ROS), induce cancer cell death through apoptosis, and prevent bacteria, fungal, and virus infections indicating their potentials. This review also highlighted the challenges and opportunities of natural products in transdermal/topical delivery systems and their safety considerations for skin disorders. Our findings indicated that natural products might be a low-cost, well-tolerated, and safe treatment for skin diseases. However, a larger number of clinical trials are required to validate these findings. Natural products in combination with modern drugs, as well as the development of novel delivery mechanisms, represent a very promising area for future drug discovery of these natural leads against skin disorders.